The heavy rain differences based on topo-geographical analyse at Coastal Central Region, from Thanh Hoa to Khanh Hoa - Van, Nguyen Khanh; Tuan, Tong Phuc; Vu, Vuong Van; Ha, Nguye Manh (Vietnam Journal of Earth Sciences, 2014)
Following the article “The Role of topo-geographical conditions of Northern Central Region Vietnam and the difference of heavy rains between North and South Ngang Pass” [Journal of Sciences of the Earth T.34, N°1/2012], this paper present the reseach results of the resonant influences of topo-geographic conditions in heavy rains patterns in Coastal Central Region of Vietnam, those divided into some areas along N-S direction by E-W orientation mountain ranges (Ngang, Hai Van, Ca passes). Base on the weather situation maps, daily rainfall data (1987-2006) over Coastal Central territory (from Thanh Hoa to Khanh Hoa), the count and frequencies of heavy rains occurrence (during this timeline) corresponding to 7 types of 309 Synoptic Weather Situation (SWS) - major factor leading to heavy rain - have been analised and evaluated. The results of analysing simultaneously topo-geographic conditions of 4 areas: Northern Ngang Pass (KV1), Ngang Pass to Hai Van Pass (KV2), Hai Van Pass to Ca Pass (KV3) and Southern Ca Pass (KV4) together with SWS show that: - For the heavy rain caused purely by cold air mass (CAM): in KV1: there are only 7 waves equivalent 10,4% of total number of SWS, while in KV2 there are 41 waves - accupeid 36,9%, in KV3: 11 weves ∼ 19,3%, and in KV4 there are 13 waves ∼ 38,2%. - For the heavy rain caused by CAM and combination of CAM with other SWS: in KV1 there are 8 waves (11,9% of total number of SWS), in KV2: 51 waves (accounts for 45,9%), in KV3: 37 weves (64,9%) and in KV4 there are 24 weves (70,6%). It meens the sounthern areas have higher havy rain frequence. - The differences in topo-geographic condition of 4 areas, especially the directions of mountain ranges, characteristics of major mountain ranges, the directions of coast line and the presence of some mountain passes (Ngang, Hai Van, Ca), are the main reason leading to the increasing convergence and as the consequently the noticeable increase of heavy rains frequence those relative to CAM. - The study on the heavy rain differences based on topo-geographical analyse will be a source of valuable information, contributing to more precisely forecast of heavy rains in different areas of Coastal Central Region of Vietnam. The above approach of geographic climatology to examine the topo-geographical conditions and heavy rains is a new and reasoable approach, it allows to solve the natural disaster problem more effective and more useful at difference areas in Coastal Central Region of Vietnam. The study was supported by 2 projects of Vietnam Academy of Science and Technology [7, 8], Science brench "Preventing Disaster Reduction", performed in the years 2008-2009 and 2012-2013.